2016
DOI: 10.1111/zsc.12227
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected hybridization patterns in Near Eastern terrapins (Mauremys caspica, M. rivulata) indicate ancient gene flow across the Fertile Crescent

Abstract: U. (2017). Unexpected hybridization patterns in Near Eastern terrapins (Mauremys caspica, M. rivulata) indicate ancient gene flow across the Fertile Crescent. -Zoologica Scripta, 46, 401-413.Recent studies indicate that hybridization in animals occurs more frequently than previously thought and that it may play an important evolutionary role. Chelonians are capable of extensive hybridization, raising the question how chelonian species evolve and maintain genetic integrity despite hybridization. Here, we use tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…refugia (Djamali et al, 2012). However, the ranges of two eastern Mediterranean and Middle Eastern terrapin species (Mauremys caspica, M. rivulata) also have shifted only little since the LGM (Vamberger et al, 2016), suggesting that the pattern revealed for T. graeca may be not unique and that further ectothermic species from the Middle East should be examined to elucidate these unexpected patterns in more detail. Our results of the species distribution models agree with our demographic analyses, which do not corroborate the hypothesis of postglacial population expansions for the subspecies of T. graeca, in contrast to many western Palaearctic species that expanded their ranges from local glacial refugia (including species distributed in Iran; Ahmadzadeh et al, 2013;Rajaei Sh et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…refugia (Djamali et al, 2012). However, the ranges of two eastern Mediterranean and Middle Eastern terrapin species (Mauremys caspica, M. rivulata) also have shifted only little since the LGM (Vamberger et al, 2016), suggesting that the pattern revealed for T. graeca may be not unique and that further ectothermic species from the Middle East should be examined to elucidate these unexpected patterns in more detail. Our results of the species distribution models agree with our demographic analyses, which do not corroborate the hypothesis of postglacial population expansions for the subspecies of T. graeca, in contrast to many western Palaearctic species that expanded their ranges from local glacial refugia (including species distributed in Iran; Ahmadzadeh et al, 2013;Rajaei Sh et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the territory of Iran, some species experienced range contractions to glacial refugia located, for example, in the Zagros, Alborz, and Kopet Dagh Mountains, which were followed by postglacial expansion (Ahmadzadeh et al, 2013;Dianat, Darvish, Cornette, Aliabadian, & Nicolas, 2017;Rajaei Sh et al, 2013;Shahabi, Akmali, & Sharifi, 2017). Other species did not shift their range substantially since the LGM and revealed a long-term range stability (Javanbakht et al, 2017;Vamberger et al, 2017), or even showed more extensive distribution during the glacials and retraction of ranges in interglacials as was evidenced for psychrophilic mountainous species (Djamali et al, 2012). Those descended during the LGM from mountains to lower altitudes, spread widely and retracted their range toward higher altitudes in the Holocene (Djamali et al, 2012;Hewitt, 2000Hewitt, , 2004.…”
mentioning
confidence: 99%
“…If the complex interplay between these factors varies over time and space, spatial patterns in secondary contact can be very different and range from sharply defined narrow hybrid zones to patchy distributions of parental species and hybrid populations in mosaic hybrid zones (Curry, ; Jiggins & Mallet, ). In fact, there are well‐studied examples where secondary contact between the same species resulted in different patterns of admixture at different localities, such as in marine invertebrates ( Mytilus edulis , Mytilus trossulus : Riginos & Cunningham, ; Stuckas et al, ) or tortoises ( Mauremys : Vamberger et al, 2017). The sparrow hybrid system provides another striking case where differentially structured hybrid zones between the same species exist in different regions of their range of overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Using these data, 20 genotypes of each hybrid class (F1, F2, and the two backcrosses) were modeled in HYBRIDLAB 1.0. Then, the obtained simulated hybrid data were subjected to analyses using STRUCTURE, together with the data of the two parental populations from Germany and Spain (see Vamberger et al, 2017, for a similar approach).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation